Teaching and Learning As Relating: A Transformational Experience - Solomon, Margot (Auckland University of Technology, 2017)
This study aims to add to the knowledge base for teachers of psychotherapy and other helping professions through the lens of the teacher’s subjectivity. The thesis cites research that indicates that the teacher’s way of being and relating impacts on the student and thus on the clients of the student. Hermeneutic phenomenology is the methodology and method used to explore the question of how the teacher learns as she teaches. Lived experience is analysed using the hermeneutic circle, going back and forth between the parts and the whole. The focus is on the teaching of the researcher herself using journals, teaching notes, and nineteen interviews with colleagues and ex-students to uncover how the teaching and learning happens. At the centre of the study is the notion of ‘learning and teaching as relating’, namely that the relationship between the teacher and the students is intrinsic to effective teaching and learning. Negotiating the structures of the teaching course is a task for the teacher, with students and the university. It is both a pre-requisite and ongoing process of collaboration. What emerges is that in learning from experience there is some transformation for the students and, at times, the teacher. Necessary features of the teaching and learning experience are the teacher’s capacity to dwell and the journeying together, the waymaking. While any one of the four elements of the negotiated frame; learning to dwell; waymaking and learning from experience is in the foreground, the other three are also present and active. This research demonstrates the importance of valuing emotional learning, which brings the whole person of the student and the teacher into the classroom setting. Transformational learning or finding new ways of seeing the world and oneself are outcomes of this kind of teaching and learning which brings the potential for an expansion of the capacity to think and reflect in both teacher and student, thus increasing effectiveness in practice.
Keywords: Teaching; Learning; Psychotherapy; Education; Emotional learning; Reflection; Transformation